Pascal Wager Analyzing the concept in Terms of Meaning and Contest - Abd Alsattar Hasan Alsa'ady, Assist. Lecturer. (lark, 2026)
Defining concepts with precision is fundamental to presenting a coherent vision grounded in sound understanding. Without clarity in meaning, any discussion of a concept remains incomplete. This study seeks to redefine Pascal’s Wager by examining the problem of its meaning, which has been interpreted in multiple and often inconsistent ways since Pascal first articulated it.We argue that much of the confusion stems from the absence of an appropriate methodological framework capable of ensuring conceptual accuracy. Accordingly, this research adopts a contemporary analytical method—contextual analysis—to clarify the wager by situating it within the context to which Pascal himself connected it. Most prior studies, in our view, have neglected this contextual dimension.The central outcome of this study is a reconstruction of Pascal’s Wager grounded directly in Pascal’s own text, achieved through analytical examination and critical evaluation of its key concepts. At the same time, we demonstrate how alternative interpretations became inaccurate due to methodological approaches that treated the wager in isolation from its original context.
Keywords: Contextual Analytic, Wager, Existence of God.